Landing Trends, Species Composition and Percentage Composition of Sharks and Rays in Chittagong and Coxas Bazar, Bangladesh (Global Journal of Science Frontier Research, 2014)
The study was conducted from April, 2006 to June, 2010 on landing trends, species composition and percent contribution of sharks and rays by weight using the catch records of Marine Fisheries Survey Management Unit, Chittagong from two landing centers Fishery ghat, Chittagong and BFDC ghat, Cox's Bazar. This study identified 27 species in total representing 11 species of shark (04 families) and 16 species of ray (09 families). The highest landing volume (134 MT) and contribution (76%) to total catch for the whole sampling period was found from Scoliodon laticaudus followed by Rhizoprionodon acutus (108 MT or 55%), Carcharhinus melanopterus (75 MT or 38%), Sphyrna zygaena (49 MT or 26%), Chiloscyllium indicum (38 MT or 20%), Eusphyra blochii (22 MT or 11%) Galeocerdo cuvier (21 MT or 10%) and other (03 MT or 2%). Species which occurred least were placed in the 'other' category comprising Carcharhinus amblyrhynchos, Stegostoma fasciatum, Carcharhinus leucas and C. falcifomis.
Keywords: shark; ray; species composition; elasmobranches fishery; landing trend; catch data; abundance; percent contribution